2011
DOI: 10.1186/1742-9994-8-21
|View full text |Cite
|
Sign up to set email alerts
|

Landmarks or panoramas: what do navigating ants attend to for guidance?

Abstract: BackgroundInsects are known to rely on terrestrial landmarks for navigation. Landmarks are used to chart a route or pinpoint a goal. The distant panorama, however, is often thought not to guide navigation directly during a familiar journey, but to act as a contextual cue that primes the correct memory of the landmarks.ResultsWe provided Melophorus bagoti ants with a huge artificial landmark located right near the nest entrance to find out whether navigating ants focus on such a prominent visual landmark for ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(110 citation statements)
references
References 45 publications
4
106
0
Order By: Relevance
“…The latter species, nesting in visually rich environment, learn visual cues more efficiently. More recently, Wystrach et al (2011b) went a step further, somewhat modifying previous affirmations. They provided M. bagoti ants with a huge artificial landmark located right near the nest entrance to find out whether navigating ants focus on such a prominent visual landmark for homing guidance.…”
Section: Discussionmentioning
confidence: 99%
“…The latter species, nesting in visually rich environment, learn visual cues more efficiently. More recently, Wystrach et al (2011b) went a step further, somewhat modifying previous affirmations. They provided M. bagoti ants with a huge artificial landmark located right near the nest entrance to find out whether navigating ants focus on such a prominent visual landmark for homing guidance.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of a moving animal, previous experience of successful visually guided foraging may render global information more robust to movement disturbance or variations in view angle, among other factors. Additionally, constructing a global landscape from local landmarks is an important navigation strategy for both bees and ants [32,[59][60][61]. Interestingly, arbitrating between local and global processing of the visual panorama, among other available cues [62][63][64], has revealed a crucial factor of navigation success [32,60].…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the geometric shape of the boundary of the environment formed by mountains could be used as an orienting cue. Indeed, the panoramic contour formed by the view of terrestrial objects against the skyline has been shown to be a potent navigational cue for foraging ants (e.g., Graham & Cheng, 2009;Legge, Wystrach, Spetch, & Cheng, 2014;Wystrach, Beugnon, & Cheng, 2011).…”
mentioning
confidence: 99%